Psychological Distress in Medical Students: Cross Sectional Study - Sumbal Khalid, Usman Amin Hotiana, Zunera Muzzamil, Samia Mumtaz, Sadia Akram (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Medical students, especially those of higher classes, are more likely to be severely distressed due to their clinical rotations. Moreover, exposure to critical patients, lack of social life and selection of speciality etc are few of the stresses in the lives of senior medical students. Aim: To assess the degree of mental stress in medical students. Study Design: Cross-sectional study. Methodology: The M.B.B.S students of higher classes, i.e., third, fourth and fifth year students, were included in the current study. The Kessler psychological distress scale was used to assess the degree of mental stress in medical students. Each questionnaires, having 10 questions, was distributed among the 230 students at Farooq Hospital Westwood, Lahore. Out of 230, 189 students filled the questionnaires. Data was evaluated by using SPSS version 20. Results: Majority of the students 36% had severe psychological distress. About 19% and 16% students had been found to have mild and moderate level of psychological distress respectively. Only 29 % students were doing well. Conclusion: It was concluded that Majority of medical students were found suffering from severe psychological distress. Keywords: Social Media, Medical Students, Mental Health and Mental Distress.